Analysis of The Effect of Work Discipline and Career Development on Organizational Commitment at Farmers Market PTC Mall Palembang - Agustin, Nency; Marnisah, Luis; Handayani, Susi (Faculty of Economics dan Business, Atma Jaya Makassar University, 2025)
This study aims to analyze the influence of work discipline and career development on employees' organizational commitment at Farmers Market PTC Mall Palembang. Using a quantitative approach with SPSS version 26, this research was conducted through a survey method by distributing questionnaires to 102 employees selected as samples from the total population of Farmers Market PTC Mall Palembang employees. The collected data were analyzed using multiple linear regression to examine the relationship between the studied variables. The results indicate that work discipline and career development have a positive and significant effect on employees' organizational commitment. Employees with a high level of discipline tend to have a greater sense of responsibility towards the organization, while well-structured career development programs, such as training and promotion opportunities, enhance loyalty and work motivation. These findings provide recommendations for the company to focus more on improving discipline strategies and career development programs to create a more productive and sustainable work environment.